Artistic explorations of the brain - Fetz, Eberhard E. (Frontiers in Human Neuroscience, 2012)
The symbiotic relationships between art and the brain begin with the obvious fact that brain mechanisms underlie the creation and appreciation of art. Conversely, many spectacular images of neural structures have remarkable aesthetic appeal. But beyond its fascinating forms, the many functions performed by brain mechanisms provide a profound subject for aesthetic exploration. Complex interactions in the tangled neural networks in our brain miraculously generate coherent behavior and cognition. Neuroscientists tackle these phenomena with specialized methodologies that limit the scope of exposition and are comprehensible to an initiated minority. Artists can perform an end run around this impasse by representing the brain’s many functions in a manner that can communicate to a wide and receptive audience. This paper explores the ways that brain mechanisms can provide a largely untapped subject for artistic exploration.